Kinetics and mechanisms of ciprofloxacin cleavage in light assisted fenton reaction - Giri, Ardhendu Sekhar; Golder, Animes Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Ciprofloxacin (CIP) is a broad-spectrum antibacterial drug of fluoroquinolone class. The activity of CIP should vanish through transformation of piperazine and fluorine substituents Fenton reaction. The objective of the present study was to compare the kinetics of degradation and mineralization of CIP in light assisted Fenton reaction. The batch experiment was performed in presence of a low pressure UV lamp of 9 W at wavelength of 362 nm with 400 mL 15 mg/L CIP solution in a 1 L photo-reactor at 25°C. The molar ratio of Fe2+/H2O2 and pH were chosen as 0.125 and pH 3.5 from the experimental optimization of CIP decomposition studies. Maximum drug and mineralizing efficiency were of 97.4 and 84.1%. The rate of drug mineralization was about 5 times slower than that of CIP cleavage. Mass spectra displayed that 11 intermediates were originated upon CIP oxidation in Fenton reaction with UV irradiation. The degradation mechanism suggested that most of the intermediates were attached to the core quinolone structure. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->